BRIDGING CULTURES THROUGH HAPPINESS: A LOOK AT ENGLISH AND UZBEK LANGUAGE AND CULTURE - PhD Sh.R. Hakimova,; D.T. Ashurokhunova, (Лучшие интеллектуальные исследования, 2024)
Abstract: This article explores the role of language and culture in shaping happiness and well-being, with a focus on the English and Uzbek languages. Drawing on research in bilingualism, cognitive psychology, and language learning, the article examines how language proficiency and cultural awareness can facilitate cross-cultural communication and understanding. By exploring the unique linguistic and cultural characteristics of English and Uzbek, the article highlights the potential for language learning to bridge cultural divides and foster empathy and connection. Ultimately, the article argues that embracing linguistic diversity and cultural exchange can contribute to greater happiness and harmony in a globalized world.